KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA: TANTANGAN, PELUANG, DAN IMPLIKASINYA - Kiki Miftahul Hakiki; Ratu Suntiah; Mursidin Mursidin; Ikhsanul Fauzi; Fatih Nur Afif Ramadhan Korlin (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This article analyzes the development of Indonesian government policies related to Islamic education, focusing on the challenges,opportunities, and implications faced in its implementation. Islamic education plays an important role in teh information of character and religious values in Indonesia, the country with the largest Muslim population in the word. Government policies in Islamic education cover aspects of regulation, financing, curriculum, and empowerment of Islamic educational institutions.This article also explores the relationship between Islamic education regulations and national education policies and their impact on achieving educational goals in Indonesia.